Enhancing teaching quality through analysis tools in an international context. Findings from the Erasmus+ INA Project - Schöftner, Thomas (Sensos-e, 2025)
The cross-national Erasmus+ project "INA" investigated the effectiveness of analysis and observation sheets (AS) in four European countries (Austria, Spain, Finland, and Germany) to enhance teaching quality. In a predominantly quantitative, partly comparative design with three data collection points, N = 109 participants (56 in-service teachers, 43 students) were surveyed on their competence development and motivation. Ethical standards were followed through written informed consent and strict anonymization. Reliability (Cronbach’s Alpha a = .72–.86) and validity (expert ratings, construct validity) measures ensured robust instruments. Prolonged use of AS correlated positively with improved self-assessment and external assessment of classroom management and subject expertise, with students reporting considerable gains in social competence, resilience, and the use of didactic materials. Embedding AS into research-based learning fosters reflective practice and incremental improvements in teaching quality, although cultural differences and institutional contexts require adaptations. Future research should expand the sample to various types of schools, refine measurement tools, and further integrate qualitative methods.